2015
DOI: 10.7314/apjcp.2015.16.15.6359
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase Inhibition and Capecitabine Combination as 1stor 2ndLine Treatment for Metastatic Breast Cancer - a Retrospective Analysis

Abstract: Background: Preclinical studies have shown that the combination of an aromatase inhibitor (AI) and capecitabine in estrogen receptor (ER)-positive cell lines enhance antitumor efficacy. This retrospective analysis of a group of patients with metastatic breast cancer (MBC) evaluated the efficacy and safety of combined AI with capecitabine. Materials and Methods: Patients with hormone receptor-positive metastatic breast cancer treated between 1st January 2005 and 31st December 2010 with a combination of capecita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Capecitabine is a cytotoxic oral drug with an adequate safety profile and strong evidence of effectiveness in MCh studies [27]. It was proven to be effective in combination with AI, showing favorable outcomes in several clinical trials [28][29][30][31][32][33]. In 2015, Shankar et al reported median progression free survival (mPFS) of 21 months for chemoendocrine therapy, 15 months for AI, and 8 months for capecitabine alone [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capecitabine is a cytotoxic oral drug with an adequate safety profile and strong evidence of effectiveness in MCh studies [27]. It was proven to be effective in combination with AI, showing favorable outcomes in several clinical trials [28][29][30][31][32][33]. In 2015, Shankar et al reported median progression free survival (mPFS) of 21 months for chemoendocrine therapy, 15 months for AI, and 8 months for capecitabine alone [28].…”
Section: Introductionmentioning
confidence: 99%
“…It was proven to be effective in combination with AI, showing favorable outcomes in several clinical trials [28][29][30][31][32][33]. In 2015, Shankar et al reported median progression free survival (mPFS) of 21 months for chemoendocrine therapy, 15 months for AI, and 8 months for capecitabine alone [28]. Moreover, a recent phase II clinical trial showed that metronomic capecitabine combined with AIs had good efficacy, minimal toxicity, and good tolerance [31].…”
Section: Introductionmentioning
confidence: 99%
“…Capecitabine was specifically designed for oral administration, to deliver 5-fluorouracil (5-FU) to the tumor site and to avoid systemic 5-FU exposure. Oral capecitabine is highly effective for the management of breast and colorectal cancer (Kaklamani and Gradishar, 2003;Shankar et al, 2015). By using a three-step enzymatic cascade, the innovative oral fluoropyrimidine carbamate capecitabine (Xeloda) preferentially produces 5-FU in tumor tissue.…”
mentioning
confidence: 99%